Electrochemical sensing and forensic applications of Dy3+-doped Sr2MgSi2O7 Nanophosphors: Phyto-mediated synthesis, morphology and DFT studies - Majani, Sanjay S.; Singh, Pallavi; Kaygili, Omer; Bulut, Niyazi; Basavaraj, R. B.; Sureshkumar, K.; Kollur, Shiva Prasad (Elsevier Science Sa, 2026)
This study reports the synthesis, characterization, and multi-performance evaluation of Dy3+-doped Sr2MgSi2O7 (SMSDx; x = 1, 3, 5, 7, and 9 mol%) nanophosphors prepared via a solution auto-combustion method using Aloe vera gel as fuel. Rietveld-refined PXRD patterns showed a dominating tetragonal phase (P-42(1) m, JCPDS Card No. 42-0932) next to a minor monoclinic phase (P2(1)/a, JCPDS Card No. 75-1736) with no notable peak shifts but varying intensity, suggesting effective Dy3+ replacement. While HRTEM projected an interplanar d-spacing of 0.285 nm, FESEM and TEM studies found quasi-spherical particles in the 29.85 nm range. Sr2+, Mg2+, Si4+, O2-, and Dy3+'s existence and oxidation states were verified by XPS and EDS. Increasing dopant concentration adjusted optical band gap values from 4.76 eV to 4.80 eV; Raman spectra showed changes in Si-O-Si and Mg-O vibrational modes caused by local lattice distortion. With SMSD3 displaying the greatest intensity, photoluminescence experiments under 352 nm excitation showed strong emissions at 483 nm (F-4(9/2) -> H-6(15/2)), 575 nm (F-4(9/2) -> H-6(13/2)), and 662 nm (F-4(9/2) -> H-6(11/2)). With a Q-value of about 6, showing dipole-dipole interaction, Dexter's hypothesis verified the concentration quenching process. Suitable for cool white-light phosphors, chromaticity study put all samples in the yellow-to-near-white area with CCT values between 4500 and 6000 K. A DOS study indicates that the interactions between the oxygen 2p and metal d orbitals govern the transitions. Additionally, DFT calculations revealed distinct electrical properties for each phase, with phase I exhibiting a direct band gap of 4.602 eV, while phase II has an indirect band gap of 4.969 eV. Conventional powder dusting forensic assessment revealed obvious Type-III level latent fingerprint visibility on surfaces, including ceramic, glass, and metal. Electrochemical sensing through CV and impedance studies, using SMSD-modified SPCEs revealed significant redox response, especially for SMSD9, with anodic/cathodic peaks at 0.57 V/0.31 V and large current densities for paracetamol oxidation, verifying diffusion-adsorption controlled two-electron, two-proton transfer. The Liner dynamic range (LDR) and limit of detection obtained for paracetamol were 0-10 mu M and 0.2945 mu M respectively. The sensor demonstrated commendable recovery (similar to 92.4 %) for paracetamol from acidified real water samples over a 15-day period, confirming its precision, dependability, and short-term operational stability in practical settings. The results show SMSDx nanophosphors as flexible nanophosphors linking luminous, forensic, and electrochemical domains-providing a hopeful answer to the rising need for application-integrated multifunctional materials.
Keywords: Nanophosphors; Electrochemical sensor; Forensics; SDG 6; SDG 7